Can sugar metabolism in the cambial region explain the water deficit tolerance in poplar?. (26th May 2018) - Traversari, Silvia; Francini, Alessandra; Traversi, Maria Laura; Emiliani, Giovanni; Sorce, Carlo; Sebastiani, Luca; Giovannelli, Alessio
Abstract : In two poplar species with contrasting growth performance, sugar metabolism in xylem and cambial regions can explain their different grades of tolerance to drought and their recovery rates following water deficits. Abstract: Drought dramatically affects wood production by adversely impacting cambial cells and their derivatives. Photosynthesis and assimilate transport are also affected by drought conditions. Two poplar genotypes, Populus deltoides 'Dvina' and Populus alba 'Marte', demonstrated contrasting growth performance and water–carbon balance strategies; a mechanistic understanding of the water deficit response was provided by these poplar species. 'Marte' was found to be more anisohydric than 'Dvina'. This characteristic was associated with the capacity to reallocate carbohydrates during water deficits. In contrast, 'Dvina' displayed more conservative water management; carbohydrates were preferably stored or used for cellulose production rather than to achieve an osmotic balance between the phloem and the xylem. Data confirmed that the more 'risk-taking' characteristic of 'Marte' allowed a rapid recovery following water deficit and was connected to a different carbohydrate metabolism.